100 MHz current generator with T/(T − t) time waveform in 0.35 μm BiCMOS technology. Issue 9 (1st April 2016) - Tadić, N.; Goll, B.; Zimmermann, H.
Abstract : A 0.35 μm BiCMOS current generator suitable for optical quantum random number generators is presented. The time dependence of the current pulses is of the form T /( T − t ). The design uses the bipolar junction transistor translinear loop with two inputs supplied by a DC and one input supplied by a sawtooth current. The relative error of the measured waveform at 20 MHz is <3% in 97.5% of the time interval in which the current pulses have a rising slope. The current pulses can be generated up to a frequency of 100 MHz.